2020
DOI: 10.1111/jphp.13264
|View full text |Cite
|
Sign up to set email alerts
|

Design of enamides as new selective monoamine oxidase-B inhibitors

Abstract: Objectives To develop of new class of selective and reversible MAO-B inhibitors from enamides. Methods Syntheses of the titled derivatives (AD1-AD11) were achieved by reacting cinnamoyl chloride and various primary and secondary amines in basic medium. All eleven compounds were investigated for in vitro inhibitory activities against recombinant human MAO-A and MAO-B. The reversibilities of lead compound inhibitions were analysed by dialysis. MTT assays of lead compounds were performed using normal VERO cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
(56 reference statements)
2
12
0
Order By: Relevance
“…The results were coincided to the studies that the rational design of two phenyl/heteroaryl rings connected via a short linker could lead to potent inhibitors targeting MAO-B and MAO-A. [31,32] Recently, Mathew et al reported that fluorinated morpholine-based chalcones (f1-f3) exhibited potent inhibitory activity and high SI towards recombinant human MAO-B (IC 50 = 0.21 to 0.087 μM; SI = 47.6 to 517.2). [24] The molecular selectivity could be also modulated on the basis of electron donating and withdrawing substitutions on the rings and depended on the length and the degree of conjugation of linker.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The results were coincided to the studies that the rational design of two phenyl/heteroaryl rings connected via a short linker could lead to potent inhibitors targeting MAO-B and MAO-A. [31,32] Recently, Mathew et al reported that fluorinated morpholine-based chalcones (f1-f3) exhibited potent inhibitory activity and high SI towards recombinant human MAO-B (IC 50 = 0.21 to 0.087 μM; SI = 47.6 to 517.2). [24] The molecular selectivity could be also modulated on the basis of electron donating and withdrawing substitutions on the rings and depended on the length and the degree of conjugation of linker.…”
supporting
confidence: 79%
“…Comparatively, it was less toxic than our previous reported compounds. [32] The therapeutic potential of the compound might be suitable with a low toxic profile on the normal cells.…”
mentioning
confidence: 99%
“…Residual activities were determined before (A U ) (i. e., undialyzed) and after (A D ) dialyzing and compared to controls (i. e., without inhibitor). [41] Inhibitions of MAO-A by CD3 and CD8 were substantially recovered from 39 % (A U ) to 90 % (A D ), and from 43 % to 63 %, respectively, and these values were similar to those obtained for the reversible inhibitor toloxatone (39 to 91 % and 35 to 90 %, respectively) ( Figures 2A & 2B). Dialysis recovered inhibition of MAO-B by CD8 from 42 % (A U ) to 80 % (A D ), and this was similar to that observed for the reversible inhibitor lazabemide (42 to 81 %) ( Figure 2C).…”
supporting
confidence: 75%
“…Dialysis experiments were performed by preincubating enzyme and inhibitors, i. e., MAO‐A inhibitions by CD3 and CD8 , of MAO‐B by CD8 , and of AChE by CD10 , (or references) at ∼2×IC 50 in 0.1 M sodium phosphate buffer (pH 7.2) for 30 min and dialyzing for 6 h (with a buffer change after 3 h) with stirring. Residual activities were determined before (A U ) (i. e., undialyzed) and after (A D ) dialyzing and compared to controls (i. e., without inhibitor) [41] . Inhibitions of MAO‐A by CD3 and CD8 were substantially recovered from 39 % (A U ) to 90 % (A D ), and from 43 % to 63 %, respectively, and these values were similar to those obtained for the reversible inhibitor toloxatone (39 to 91 % and 35 to 90 %, respectively) (Figures 2A & 2B).…”
Section: Methodsmentioning
confidence: 99%
“…In the exploration of novel, selective, and reversible MAO-B inhibitors, a general blueprint of drug design has been widely accepted recently, and it consists of a molecular framework of two hydrophobic rings of phenyl/heteroaryl, which are separated by an electron-rich and flexible short spacer unit ( Figure 1 ) [ 11 ]. Many of the molecules from this diverse class, such as pyrazolines, enamides, carboxamides, and α, β-unsaturated ketones, were identified as potent MAO-B inhibitors [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The presence of a rotatable bond and electron-rich Michael acceptor unit in the spacer can efficiently make appropriate orientations and binding affinities in the entrance and substrate cavity of MAO-B.…”
Section: Introductionmentioning
confidence: 99%